Determinants of Farmer’s Financing Participation in Sharia Microfinance Institutions - Tampubolon, Dahlan; Mardiana, Mardiana; Zen, Iriana Safitri (IKONOMIKA, 2021)
This study aims to analyze the determinants of farmer participation in sharia microfinance institutions.  The study area covers Siak Regency and Bengkalis Regency, Riau Province. Respondents were taken as many as 30 respondents in Siak and 32 respondents in Bengkalis. The probit regression model is used to explain the factors that influence farmer participation in sharia microfinance institutions. Farmer loans are used for working capital, buying seeds and daily necessities. Most of the financing is wakalah wal mudhárabah and very few borrows in the form of wakalah wal musháraka. The results showed that the factors that influence farmer participation are education, dependency ratio, value of liquid assets owned, and farmers' income. The farther the farmer's house is from the location of the shariah microfinance institution, the less opportunity to participate. Other independent variables included in the model have no significant effect on farmers' opportunities to participate in sharia microfinance institutions in the two districts.